2022
DOI: 10.3390/jcm11195778
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Is an Independent Risk Factor for Subsequent Osteoporotic Vertebral Fractures Following Percutaneous Cement Augmentation in Elderly Patients

Abstract: Introduction: Subsequent osteoporotic vertebral fractures (SOVF) are a serious complication of osteoporosis that can lead to spinal deformity, chronic pain and disability. Several risk factors have been previously identified for developing SOVF. However, there are conflicting reports regarding the association between sarcopenia and multiple vertebral compression fractures. As such, the goal of this study was to investigate whether sarcopenia is an independent risk factor of SOVF. Methods:This was a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Sarcopenia is associated with higher risk of falls and fractures [ 43 ], and is a major risk factor for loss of independence in older adults [ 44 ]. In addition, many studies reported that sarcopenia was associated with vertebral fracture [ 20 , 32 , 45 47 ]. The above results are consistent with those of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is associated with higher risk of falls and fractures [ 43 ], and is a major risk factor for loss of independence in older adults [ 44 ]. In addition, many studies reported that sarcopenia was associated with vertebral fracture [ 20 , 32 , 45 47 ]. The above results are consistent with those of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary research indicates a substantial interrelationship between sarcopenia and osteoporosis, which reciprocally exacerbate one another, culminating in detrimental consequences such as falls and fractures 21 . Sarcopenia is widely acknowledged as an independent risk factor for OVCF, impacting the prognosis distinct from osteoporosis 22 . Contrarily, some academics contend that sarcopenia, through its intimate association with osteoporosis, enhances the likelihood of OVCF, though it is not an independent risk factor 23 .…”
Section: Discussionmentioning
confidence: 99%
“… 24 Lidar et al analyzed the data of 237 patients with OVCFs who underwent PKP and found that sarcopenia was an independent risk predictor of refracture in OVCF patients after PKP (OR 2.271; 95% CI 1.069–4.824; P = 0.033). 25 Overall, clarifying the effect of sarcopenia on the clinical outcomes of patients with OVCF after PKP is of great clinical significance. In this study, we compared clinical and radiological outcomes between the SPKP and NPKP groups.…”
Section: Discussionmentioning
confidence: 99%